Effect of Design Thinking Based on The PjBL Model on Students' Creative Thinking in Science Learning: A Bibliometric Analysis - Dewi, Sonia Citra; Putri, Widia Eka; Wedy, Zahra Salsabila; Asrizal, Asrizal; Agusti, Hafiz Almahfuz (Department of Physics Universitas Negeri Padang, 2024)
The purpose of this study is to analyze the collaboration pattern and the impact of the Project-Based Learning (PjBL) model based on design thinking on student creativity. The method used in this study is the bibliometric analysis method on articles from 2019-2024 totaling 100 articles. The articles used were obtained using the Publish or Perish database using VOS Viewer software. VOS Viewer visualization can display bibliometric data analysis mapping in three types, namely network visualization, overlay visualization, and density visualization. There are three research results obtained, namely 1) based on network visualization, the design thinking cluster still has minimal research related to this, but it is related to the PjBL model and creative thinking skills, 2) based on overlay visualization, the keyword design thinking has only emerged since 2022, and 3) based on density visualization, the term that has not been widely studied is design thinking. The results of the analysis show that the PjBL model based on Design Thinking is still rarely used in learning. In fact, the learning model with design thinking is able to increase student creativity, strengthen skills, and improve learning models. Therefore, research on the effect of using the Project-Based Learning (PjBL) model based on design thinking on student creativity in learning is included in the novelty in research so that more in-depth research is needed to prove the increase in students' creative thinking skills.